1994
DOI: 10.1128/iai.62.2.529-535.1994
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of hydrogen peroxide and the lactoperoxidase-hydrogen peroxide-thiocyanate system against oral streptococci

Abstract: In secreted fluids, the enzyme lactoperoxidase (LP) catalyzes the oxidation of thiocyanate ion (SCN-) by hydrogen peroxide (H202), producing the weak oxidizing agent hypothiocyanite (OSCN-), which has bacteriostatic activity. However, H202 has antibacterial activity in the absence of LP and thiocyanate (SCN-). Therefore, LP may increase antibacterial activity by using H202 to produce a more effective inhibitor of bacterial metabolism and growth, or LP may protect bacteria against the toxicity of H202 by conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(58 citation statements)
references
References 26 publications
5
50
0
1
Order By: Relevance
“…Another study reported that the combination of alum with antibiotics (tetracycline and cefotaxime) was more effective than antibiotic combination and the combination effect was more efficient than an individual effect [40]. Similarly, hydrogen peroxide in combination with lactoperoxidase and thiocyanate is reported much more effective than hydrogen peroxide alone as an inhibitor of bacterial metabolism and growth [41]. Thus, the combination strategy provides us with an opportunity to improve their efficacy at low concentration.…”
Section: Table 2 Antibacterial Susceptibility Of Selected Bacteria Amentioning
confidence: 99%
“…Another study reported that the combination of alum with antibiotics (tetracycline and cefotaxime) was more effective than antibiotic combination and the combination effect was more efficient than an individual effect [40]. Similarly, hydrogen peroxide in combination with lactoperoxidase and thiocyanate is reported much more effective than hydrogen peroxide alone as an inhibitor of bacterial metabolism and growth [41]. Thus, the combination strategy provides us with an opportunity to improve their efficacy at low concentration.…”
Section: Table 2 Antibacterial Susceptibility Of Selected Bacteria Amentioning
confidence: 99%
“…Darout et al (81) hypothesized that thiocyanate leaching out from miswak while in the oral cavity may lead to an elevated level of salivary thiocyanate. This, in turn, may enhance the ecacy of the salivary hydrogenperoxide-peroxidase-thiocyanate system, a known antimicrobial component of human saliva (84,85). This may partly explain the observation that adult Sudanese miswak users had signi®cantly lower numbers of cariogenic bacteria, except S. mutans, in their saliva while the matched toothbrush users demonstrated lower salivary levels of periodontopathogens (Darout et al 2000, unpublished observations).…”
Section: Salvadora Persica Miswakmentioning
confidence: 99%
“…Therefore their destroying effect is expected to be low (3). However, lower concentration of ROS can stimulate different biochemical pathways in the cells causing cell survival and proliferation (Imlay and Linn 1987;Thomas et al 1994;Miller and Britigan 1997;Davies 1999;Ruiz-Gines 2000;Palma et al 2004;Salunkhe et al 2005;Bartosz 2009). The two distinct effects of laser applications were studied in independent tracts in the literature, that is, proliferation effect for the cells (Karu et al 1995) or inhibitory/ killing effect for unwanted cancer cells (Tseng et al 2003;Almeida et al 2004;Crescenzi et al 2004).…”
Section: Resultsmentioning
confidence: 99%